2014
DOI: 10.1590/2176-9451.19.5.045-053.oar
|View full text |Cite
|
Sign up to set email alerts
|

Measurement accuracy and reliability of tooth length on conventional and CBCT reconstructed panoramic radiographs

Abstract: INTRODUCTION: This in vivo study assessed accuracy and reliability of tooth length measurements obtained from conventional panoramic radiographs and CBCT panoramic reconstructions to that of a digital caliper (gold standard). METHODS: The sample consisted of subjects who had CBCT and conventional panoramic radiographic imaging and who required maxillary premolar extraction for routine orthodontic treatment. A total of 48 teeth extracted from 26 subjects were measured directly with digital calipers. Radiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
0
23
0
4
Order By: Relevance
“…They also concluded that the orientation of the skull at the time of the scanning does not affect the accuracy or reliability of the landmark measurements. Flores-Mir et al (25) compared tooth length measurements from conventional panoramic radiographs and CBCT reconstructions to those taken with a digital caliper. Forty-eight extracted teeth were measured with digital calipers, and the radiographs were scanned and measured in Dolphin 3D.…”
Section: Kim Et Al (35)mentioning
confidence: 99%
“…They also concluded that the orientation of the skull at the time of the scanning does not affect the accuracy or reliability of the landmark measurements. Flores-Mir et al (25) compared tooth length measurements from conventional panoramic radiographs and CBCT reconstructions to those taken with a digital caliper. Forty-eight extracted teeth were measured with digital calipers, and the radiographs were scanned and measured in Dolphin 3D.…”
Section: Kim Et Al (35)mentioning
confidence: 99%
“…When comparing any radiographic imaging techniques used in the oral region, one should consider that all of them may carry some degree of inaccuracy when estimating the size of anatomical structures . In the present study, we aimed at assessing the reliability of CBCT for quantitative evaluation of the size of pulp chamber and related structures, by a comparison with direct microscopic evaluation of the same region.…”
Section: Introductionmentioning
confidence: 99%
“…Endodontically, it helps in assessing the working length. In prosthetics it helps in making better judgment about the selection of abutment and in periodontics it helps in comparing tooth length or root length and alveolar crestal levels [1][2][3]. Several methods of determining tooth length exists [2], but most preferred way of determining the root canal length is by radiographs mainly by the intraoral periapical radiography and orthopantomography.…”
Section: Introductionmentioning
confidence: 99%